PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA AUGMENTED REALITY PADA POKOK BAHASAN ALAT OPTIK - Wenggita Maulani Putri; Fauzi Bakri; Andreas Handjoko Permana (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
This reaserch aims to develop the instructional media Augmented Reality-based on the Optical Instruments subject. The method which used in this study is a research and develompment methods using development reaserch model by Dick and Carey. The steps are: 1) need analysis, 2) develop instructional media based Augmented Reality, 3) validation the product, 4) field trial with students from Senior High School. The validation data of instructional media using assesment instrument with Likert scale. The result of this study is a software for Android with Augmented Reality- based technology on Optical Instruments subject . This learning media Augmented Reality-based has been through a validation test with the percentage 90,54% by physics expert, 91,42% by instructional media expert, and 97,26% by physics teacher of Senior High School. The limited field test by 7 10th grade students in 22 Senior High School has reached 87,70%. The field test by 33 10th grade students in 22 Senior High School and 28 11th grade students in 33 Senior High School has reached 86,43%. As a result, learning media Augmented Reality-based has been qualified with very good quality for use as media supporting in learning physics on the Optical Instruments subject. Keywords: Instructional Media, Multimedia, Augmented Reality, Optical Instruments.